Exploring the level of academic procrastination and possible coping strategies among medical students - Manya Tahir; Rahila Yasmin; Muhammad Wajih Uddin Butt; Seema Gul; Sidra Aamer; Nabeela Naeem (Journal of the Pakistan Medical Association, 2022)
Objective: To identify the level of procrastination in undergraduate medical students and to explore the coping strategies adopted by low procrastinators to overcome the tendency. Methods: The mixed method, sequential explanatory study was conducted at the Islamic International Medical College, Riphah International University, Rawalpindi, Pakistan, from April to September 2019, and comprised medical students from preclinical first, second and third years of the academic programme. The pre-validated Academic Procrastination Scale was used to assess the prevalence and level of procrastination in the subjects, followed by semi-structured interviews with students having low level of procrastination to explore the coping strategies used by them to beat the negative habit. Data was analysed using SPSS 21 and was further subjected to manual thematic analysis. Results: Of the 255 subjects, 85(33.3%) each were in the first, second and third year of undergraduate medical studies. Overall, the level of procrastination was high in 134(52.5%) students and low in 121(47.5%). The low procrastinators were 43(51%) in the 1st year, 46(54%) in the 2nd year and 45(53%) in the 3rd year. On the basis of interview-based data, 10 coping strategies were identified: time management, self-regulation, establishment of priorities, self-reward, goal-setting, conducive learning environment, self-reminders, task management, self-evaluation and self- monitoring. Conclusion: Procrastination is a behavioural disorder and is prevalent in undergraduate medical students, but it can be effectively treated through effective coping strategies. Keywords: Coping, Strategies, Combat, Academic, Procrastination. Continue...